Single crystalline pyrochlore nanoparticles with metallic conduction as efficient bi-functional oxygen electrocatalysts for Zn–air batteries. Issue 1 (14th December 2016) - Park, Joohyuk; Risch, Marcel; Nam, Gyutae; Park, Minjoon; Shin, Tae Joo; Park, Suhyeon; Kim, Min Gyu; Shao-Horn, Yang; Cho, Jaephil
Abstract : We have shown that highly efficient metallic pyrochlore oxide nanoparticles (Pb2 Ru2 O6.5 ) exhibit outstanding activity as bi-functional electrocatalysts in aqueous Zn–air batteries for ORR and OER. Abstract : Oxygen reduction reaction (ORR) or oxygen evolution reaction (OER) electrocatalysts including carbon-, non-precious metal-, metal alloy-, metal oxide-, and carbide/nitride-based materials are of great importance for energy conversion and storage technologies. Among them, metal oxides ( e.g., perovskite and pyrochlore) are known to be promising candidates as electrocatalysts. Nevertheless, the intrinsic catalytic activities of pyrochlore oxides are still poorly understood because of the formation of undesirable phases derived from the synthesis processes. Herein, we present highly pure single crystalline pyrochlore nanoparticles with metallic conduction (Pb2 Ru2 O6.5 ) as an efficient bi-functional oxygen electrocatalyst. Notably, it has been experimentally shown that the covalency of Ru–O bonds affects the ORR and OER activities by comparing the X-ray absorption near edge structure (XANES) spectra of the metallic Pb2 Ru2 O6.5 and insulating Sm2 Ru2 O7 for the first time. Moreover, we followed the interatomic distance changes of Ru–O bonds using in situ X-ray absorption spectroscopy (XAS) to investigate the structural stabilities of the pyrochlore catalysts during electrocatalysis. The highly efficient metallic Pb2 Ru2 O6.5 exhibited outstanding bi-functional catalytic activities and stabilities for both ORR and OER in aqueous Zn–air batteries.